Novčana naknada nematerijalne štete za duševne bolove zbog smrti i teškog invaliditeta bliskog lica - Manić, Samir (Zbornik radova Pravnog fakulteta u Novom Sadu, 2012)
U ovom radu detaljno je istražen, analiziran i izložen problem nоvčаne nаknаde nematerijalne štete zа dušеvnе bоlоvе zbog smrti i teškog invaliditeta bliskog lica. Analizirane su i izložene odredbe pravilnika koje su Vlade i Vrhovni sudovi bivših jugoslovenskih republika doneli u cilju ujednačavanja sudske prakse po pitanju pravilnog utvrđivanja visine novčane naknade nematerijalne štete. Svakako, predmet ovog rada je i Uredba Vlade Republike Srbije o naknadi štete na licima. In this paper, an issue of money compensation for non-pecuniary damages for emotional distress over the death and severe disability of someone close has been researched, analyzed and presented in details. The provisions of Regulation brought by the Government and Supreme Courts of the ex-Yugoslav republics in the aim of leveling of court practice in the issue of a regular determination of a fee for non-pecuniary money compensation have also been analyzed and exposed. Certainly, the subject of this paper is the Regulation of the Government of the Republic of Serbia on compensation to third parties, either.